Implicaciones de la Autoeficacia en el rendimiento deportivo. - Guillén Rojas, Natalia (2022)
Competitive or high competition sports demands, mobility , physiological and psychological conditions that must be acquired during the training process, even during the sporting initiation process. The scientific literature has shown a growing interest to relate the self- efficacy with the sporting outcomes. Those studies have increased our understanding of this much promoted mental skill. The goal of presenting this work is to expose the psychological and behavioural implications of self-efficacy in the sport performance in any sporting modality